Global biogeography of fungal and bacterial biomass carbon in topsoil. (December 2020) - He, Liyuan; Mazza Rodrigues, Jorge L.; Soudzilovskaia, Nadejda A.; Barceló, Milagros; Olsson, Pål Axel; Song, Changchun; Tedersoo, Leho; Yuan, Fenghui; Yuan, Fengming; Lipson, David A.; Xu, Xiaofeng
Abstract: Bacteria and fungi, representing two major soil microorganism groups, play an important role in global nutrient biogeochemistry. Biogeographic patterns of bacterial and fungal biomass are of fundamental importance for mechanistically understanding nutrient cycling. We synthesized 1323 data points of phospholipid fatty acid-derived fungal biomass C (FBC), bacterial biomass C (BBC), and fungi:bacteria (F:B) ratio in topsoil, spanning 11 major biomes. The FBC, BBC, and F:B ratio display clear biogeographic patterns along latitude and environmental gradients including mean annual temperature, mean annual precipitation, net primary productivity, root C density, soil temperature, soil moisture, and edaphic factors. At the biome level, tundra has the highest FBC and BBC densities at 3684 (95% confidence interval: 1678–8084) mg kg −1 and 428 (237–774) mg kg −1, respectively; desert has the lowest FBC and BBC densities at 16.92 (14.4–19.89) mg kg −1 and 6.83 (6.1–7.65) mg kg −1, respectively. The F:B ratio varies dramatically, ranging from 1.8 (1.6–2.1) in savanna to 8.6 (6.7–11.0) in tundra. An empirical model was developed for the F:B ratio and it is combined with a global dataset of soil microbial biomass C to produce global maps for FBC and BBC in 0–30 cm topsoil. Across the globe, the highest FBC is found in boreal forest and tundra while the highest BBC is in boreal forest and tropical/subtropical forest, the lowest FBC and BBC are in shrub and desert. Global stocks of living microbial biomass C were estimated to be 12.6 (6.6–16.4) Pg C for FBC and 4.3 (0.5–10.3) Pg C for BBC in topsoil. These findings advance our understanding of the global distribution of fungal and bacterial biomass, which facilitates the incorporation of fungi and bacteria into Earth system models. The global maps of bacterial and fungal biomass serve as a benchmark for validating microbial models in simulating the global C cycle under a changing climate. Highlights: Fungal and bacterial biomass distribution showed clear biogeographical patterns. Biomass of fungi and bacteria and their ratio are controlled by different factors. Global biomass carbon budget is 12 PgC for fungi and 4 PgC for bacteria in topsoil.